Effects of stressor congruence with sociotropy-autonomy using a mood induction procedure: a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Jensen, Emma Jane (Massey University, 1994)
Aaron Beck's cognitive theory of depression suggests that depression results from the activation of underlying dysfunctional attitudes, by a congruent stressor. To test the notion of congruence, thirty-five male and sixty-one female university students were classified as sociotropic or autonomous using the Sociotropy Autonomy scale. These subjects took part in a Velten Mood Induction procedure, in which half of the subjects received a congruent negative mood induction, and the other half received an incongruent negative mood induction. The dependent variables of interest were measures of negative affect and of dysfunctional thinking. Although both congruent and incongruent inductions led to an increase in negative affect and in dysfunctional thinking, the most significant increases were observed for the congruent group.
Keywords: Stress (Psychology); Social psychology; Behavior modification